Лингводидактический потенциал путеводителя как креолизованного текста - Баранова, Ирина В.; Харченкова, Людмила И. (Wydawnictwo Uniwersytetu Rzeszowskiego, 2021)
In this article, the specifics of the guidebook as a creolized text is described including its functions, structure, as well as some linguistic, and ethnic and cultural features. Besides geographic data and information about local attractions, the guidebook contains information concerning how and where you can spend your free time, as well as advertising of accommodation places, recreation zones, catering, telephone numbers and useful addresses of restaurants, hotels, museums, etc. The authors emphasize that the guidebook serves as a moderator assisting in establishing social and cultural relations between tourists and the country to visit.
Keywords: креолизованный текст; путеводитель; иллюстрации; фотографии; лингвистические стратегии; прецедентные феномены; creolized text; guidebook; illustrations; photographs; linguistic strategies; case phenomena